(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Sirakamba vatham is a clinical entity described by Sage Yugi in his treatise Yugi Vaithiya Chinthamani- 800, as one among the 80 types of Vatha diseases described in Siddha system of medicine. The study was aimed at in depth analysis of the clinical features mentioned under Sirakamba vatham of Siddha literature and to evolve standard Siddha diagnostic methods for management for Sirakamba vatham. This study was an observational, single center study with the sample size of 26, divided into Group I (control group) having normal individuals and group II (cases with Sirakkamba vatham). At the end of the study, it was concluded, that the symptoms of Sirakkamba vatham closely resembled the symptoms of Cerebro Vascular Accident especially of posterior circulation stroke.